Satua I Truna Asibak Tua Asibak Analisis Struktur, Fungsi dan Nilai - Asri Lestari Puspa Dewi, Ni Made; Supatra, I Nyoman; Duana Sutika, I Nyoman (Humanis, 2016)
Research on Truna Asibak Tua Asibak Satua is about the analysis of the structure, function and value. This analysis has the objective to reveal the structure, functions and values ??contained in the I Truna Asibak Tua Asibak Satua. This study uses a structural theory, the theory of functions and the theory of value. The methods and techniques used in this study were divided into three stages, namely: (1) methods and techniques providing data using the reading method aided by engineering transliteration and translation techniques, (2) methods and techniques of data analysis using qualitative methods and techniques of descriptive and analytical, (3) methods and techniques of presentation of the results of data analysis using informal methods and techniques of deductive and inductive. The results obtained from this study that a narrative structure that includes thirteen incidents, using the straight flashback groove and the groove is divided into five stages. Character and characterization are the main character, secondary character, and a character complementary. Background is divided into three. The themes are that of "Karmaphala", and contained the mandate of moral teachings, and karmaphala. In addition this study reveal the function and value of the function as a guide in religious life, as a function of forming the character of the child or adolescent, respect and devotion to parents, function as a medium of entertainment. Values ??contained in it includes the value of religion that is the value of philosophy, ethics, values ??ceremonies, educational value and social value.